Phonon and phonon-related properties of MgSiN2and MgGeN2ceramics: First principles studies - Sittichain Pramchu (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this work, we used density functional perturbation theory to calculate phonon frequencies, phonon dispersions, Born effective charges, infrared (IR) absorption, and Raman spectra of MgSiN 2 and MgGeN 2 . From the results, the values of phonon frequencies have the scale comparable with the values reported in the previous theoretical work. Longitudinal optical (LO) and transverse optical (TO) splitting was also included in this work. Some small alteration of phonon frequencies were then found, which is caused by LO-TO splitting at zone-center. In addition, Born effective charge calculation reveals that MgSiN 2 and MgGeN 2 have the same ionic nature compared with the previously reported ZnSiN 2 and ZnGeN 2 semiconductor. The phonon frequencies that are IR and Raman active were firstly predicted. This clarification on phonon and phonon-related properties as well as related consequences are expected to help revealing more knowledge about the nature of MgSiN 2 and MgGeN 2 in enhancing/developing the opto-electronics devices.